Answer:
The answer is (x + 3) (x - 7) = 0
Step-by-step explanation:
x² - 4x = 21
x² - 4x - 21 = 0
x² - 7x + 3x - 21 = 0
x(x - 7) + 3(x - 7) = 0
(x + 3) (x - 7) = 0
Thus, The answer is (x + 3) (x - 7) = 0
<em><u>-TheUnknownScientist</u></em>
Can you re-phrase the question
Answer:
126 = n × (n - 5)
Step-by-step explanation:
If Nikki's age is <em>n </em>and she is 5 years older than Jamie, then Jamie is 5 years younger than Nikki's <em>n </em>number of years.
Answer:
the GCF is 3 so 2b - 3k
Step-by-step explanation:
a) plug in x =2700 into the given equation and solve for y
b) plug in y = 43 into the given equation and solve for x
c) plug in y = 0 into the given equation and solve for x
hope this helps.